2018
DOI: 10.3389/fimmu.2018.01187
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor-Related Orphan Receptors: Critical Roles in Tumorigenesis

Abstract: Retinoic acid receptor-related orphan receptors (RORs) include RORα (NR1F1), RORβ (NR1F2), and RORγ (NR1F3). These receptors are reported to activate transcription through ligand-dependent interactions with co-regulators and are involved in the development of secondary lymphoid tissues, autoimmune diseases, inflammatory diseases, the circadian rhythm, and metabolism homeostasis. Researches on RORs contributing to cancer-related processes have been growing, and they provide evidence that RORs are likely to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 80 publications
(110 reference statements)
2
50
0
1
Order By: Relevance
“…A literature review reveals that RORa is a widely distributed nuclear receptor known for its regulatory activity regarding metabolism, inflammation, angiogenesis or [17,31]. Increasingly, retinoid acid receptor-related orphan receptors are being studied in the context of cancer-related processes including gastric cancer, melanoma or colorectal cancer [32]. Fu RD et al observed that a lowered RORa expression was associated with worse survival prognosis in hepatocellular carcinoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review reveals that RORa is a widely distributed nuclear receptor known for its regulatory activity regarding metabolism, inflammation, angiogenesis or [17,31]. Increasingly, retinoid acid receptor-related orphan receptors are being studied in the context of cancer-related processes including gastric cancer, melanoma or colorectal cancer [32]. Fu RD et al observed that a lowered RORa expression was associated with worse survival prognosis in hepatocellular carcinoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…45 Several types of cancer are linked to an increase or decrease in the activity of all three RORs (reviewed in ref. 46) as well. In short, RORa showed tumor suppressive activities that were amongst others mediated by p53 (ref.…”
Section: Biological Roles Of Rorsmentioning
confidence: 94%
“…RORg and especially its isoform RORgt are the most researched RORs due to their connection to various inammatory and autoimmune diseases such as multiple sclerosis, 51 rheumatoid arthritis (RA), 52 systemic lupus erythematosus (SLE), 53 psoriasis, 54,55 asthma, 56,57 and, again, cancer 46,58,59 (also reviewed in ref. 60).…”
Section: Biological Roles Of Rorsmentioning
confidence: 99%
“…Another patient displayed a RICTOR-CCDC152 fusion (Figure 5C and D). A fusion transcript RORA-LHFP composed of RORA exon 1 fused to LHFP exon 3 is shown in Figure 5E and F. The three fusion genes are speculated to be involved in tumor growth, as their partners have important roles in malignant diseases (24)(25)(26).…”
Section: Pseudogenes Are Involved In Formation Of Gene Fusionmentioning
confidence: 99%
“…Gene fusions provide important clues for targeted therapy (26). In UPS, the data on fusion gene-guided therapy are limited.…”
Section: Confirmation Of the Rb1-fgf14-as1 Fusion By Rt-pcr For Patmentioning
confidence: 99%